The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Genre et citoyenneté culturelle à San Francisco : subjectivité et « estime de soi » dans l’organisation de la communauté latino immigrante - Coll, Kathleen (Anthropologie et Sociétés, 2009)
Cet article reconfigure la citoyenneté culturelle en termes féministes en analysant comment un groupe d’activistes latino-américaines immigrantes de la Californie du tournant du XXIe siècle parvient à revendiquer des droits politiques, sociaux et individuels. Des concepts associés d’habitude au néolibéralisme, comme par exemple la notion d’estime de soi (autoestima), ont joué un grand rôle dans les analyses hautement politisées que ces femmes font de la société américaine et des politiques sociales et d’immigration. La réutilisation créative de ces termes par les femmes implique que l’on comprenne la dynamique subversive autant que conservatrice du discours et des pratiques politiques démocratiques dans les mouvements pour les droit des immigrants contemporains, ainsi que les racines de l’activisme actuel, qui s’inscrit dans des actions à long terme dans le but de transformer la subjectivité politique.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; citoyenneté; cours; discipline; droits des femmes*; femmes immigrantes; femmes latino-américaines; militance; participation politique; périodes historiques; régions géographiques; sciences humaines; soc1061; thématiques; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis